Periosteal Fixation Procedures in the Management of Incomitant Strabismus - Saxena, Rohit (Middle East Afr J Ophthalmol, 2015)
Managing a case of incomitant strabismus from nerve palsy or extraocular muscle loss is a major challenge. Among possible management options are globe or extraocular muscle fixation to the orbital wall coupled with weakening or strengthening of the relevant antagonist. Extraocular muscle fixation to the orbital wall can also be used in cases of abnormal synkinesis to eliminate the abnormal eye movements of a misfiring extraocular muscle, which thereby allows the use of standard paralytic strabismus surgery techniques. This review article summarizes indications and techniques of periosteal fixation procedures for incomitant strabismus.